Spontaneous gastric perforation in 11-year-old boy with anorexia nervosa: rare presentation with right iliac fossa pain. (30th November 2012) - Darji, Parth; Gandhi, Viplav; Banker, Hiral; Chaudhari, Hemang D
Abstract : Spontaneous gastric perforation is rare in children. It is usually associated with prematurity, foreign bodies and trauma. Anorexia nervosa (AN) can be an underlying condition although no cases are reported in the literature. We are reporting a rare case of 11-year-old boy with AN who presented with right iliac fossa pain mimicking acute appendicitis. Intraoperative findings proved a gastric perforation. Pathophysiology of this condition in AN is poorly understood. Gastric smooth muscle atrophy and ischaemia can be the possible underlying mechanisms. The case discussed here highlights the fact that any abdominal pain in patients with underlying eating disorders should raise suspicion of perforation as diagnosis can be far more complicated.